Rancang Bangun Sistem Informasi Inventaris Barang Pada SMKN 1 Parittiga - Sundara, Ayu; Andriyanto, Sidhiq; Pratama, M. Setya (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
This research aims to design and build a web-based goods inventory system at SMKN 1 Parittiga to assist the goods inventory section in submitting goods, information on incoming and outgoing goods and the condition of the goods. The research method used is a descriptive qualitative method and the data collection method is the method of observation, interviews, literature and documentation and uses the waterfall method as a software development method. This web-based inventory information system at SMKN 1 Parittiga was built using sublime text PHP, Bootstrap, CI, database, and MySQL programming languages. The goods inventory information system at SMKN 1 Parittiga makes it easy for admins to submit goods, information on incoming and outgoing goods, and information on the condition of goods. For this reason, in this project, analysis and design of the system have been carried out, with the final result that this inventory information system has proven to facilitate and greatly assist the performance of the inventory section.